Productivity Improvement of Production Unit Using Objective Matrix (OMAX) Method at PT. X - Kotimah, Khusnul; Aryanny, Enny (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT. X is one of the industries in Indonesia that processes sugar cane into sugar and is one of the suppliers of national sugar needs. PT. X's production activities in 2022 still cannot reach the target and production per period has fluctuated. Therefore, this study was conducted with the aim of knowing the current level of total and partial productivity and can provide suggestions for improvement to increase the productivity of sugar production at PT. X in the future. The method used is Objective Matrix (OMAX) with the determination of the weight of the criteria using the AHP method. The criteria used in this study are raw materials, labor, boiler machine working hours, electricity and water. Based on the calculations that have been carried out, it can be seen that partial productivity on raw material criteria, the best productivity ratio owned by the company is 6.97, on labor criteria the ratio is worth 1521.86, on the criteria for boiler machine working hours worth 978.91. In the electricity criteria, the best productivity ratio is 3.89. In the water usage criteria, the highest productivity value is 1.83. The company's highest total productivity achieved was 750.7 in the 6th period of August and the lowest productivity with a value of 73.8 in the 2nd period of June. Improvements were made to all criteria, especially labor criteria and boiler machine working hours. With the application of the OMAX method, PT. X can improve partial productivity and total productivity in the future and identify factors that cause productivity to drop in a certain period.